Apoptotic activity of new oxisterigmatocystin derivatives from the marine-derived fungus aspergillus nomius NC06 - Artasasta, Muh. Ade; Yanwirasti, Yanwirasti; Bakhtiar, M. Taher; Djamaan, Akmal; Ariantari, Ni Putu; Ru Angeli, Edrada Ebel; Handayani, Dian (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Sponge-derived fungi have recently attracted attention as an important source of interest- ing bioactive compounds. Aspergillus nomius NC06 was isolated from the marine sponge Neopetrosia chaliniformis. This fungus was cultured on rice medium and yielded four compounds including three new oxisterigmatocystins, namely, J, K, and L (1, 2, and 3), and one known compound, asper- gillicin A (4). Structures of the compounds were elucidated by 1D and 2D NMR spectroscopy and by high-resolution mass spectrometry. The isolated compounds were tested for cytotoxic activity against HT 29 colon cancer cells, where compounds 1, 2, and 4 exhibited IC50 values of 1.21, 2.23, and 5.62 μg/mL, respectively. Under the fluorescence microscope by using a double staining method, HT 29 cells were observed to be viable, apoptotic, and necrotic after treatment with the cytotoxic compounds 1, 2, and 4. The result shows that compounds 1 and 2 were able to induce apoptosis and cell death in HT 29 cells.